Ta’thīr Istikhdām al-Biṭāqah al-Wamḍiyah bi al-Ḥurūf al-Hijā’iyyah fī Istīʿāb al-Mufradāt al-ʿArabiyyah - Nabil Latif (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Lack of vocabulary is a problem while learning a language for non-native speakers since it results in speech weakness. Due to their inability to comprehend what they were being taught and lack of enthusiasm, the pupils found it difficult to regurgitate the terminology. The Alphabet Flash Card Tool was created to make learning enjoyable. In addition to graphical features, it is a device that makes it simpler for pupils to comprehend the lesson so they can obtain better outcomes (writing and pictures). Quantitative field research, an experimental design, and statistical methods are the research techniques used. After conducting the post-test comparing the two groups in this study, the researcher discovered the results: the experimental class had an average score of (77,5), while the control class had an average score of (65,90). The researcher discovered a result that is superior to the result in the table (Tt) in the degree of 5% = 1.99 and has a t-test result (To) = 2.36. Finally, the second semester vocabulary comprehension of the pupils at Muhammadiyah Langsa Intermediate School is affected by the use of the alphabetical flashcardsقلة المفردات عند تعلم اللغة العربية يسبب ضعف في الكلام. وكذلك المشكلات في هذا البحث هي ضعف في نطق الحروف لدى الطلاب بسبب ذلك وجد الطلاب الصعوبة في تكرار المفردات وقلة الفهم وقلة رغبة الطلاب في التعليم اللغة العربية. الغرض من أداة بطاقة الومضية بالحروف الهجائية يجعل عملية التعليم ممتعة. هي آلة تسهل على الطلاب فهم الدرس حتى يتمكنوا من تحقيق نتائج أعلى، بالإضافة إلى وسائل الراحة الرسومية يعني تدريب الكتابة بالصور. والمنهج البحث المستخدم هو البحث الميدان الكمي بالنوع التجريبي، وبالطريقة الإحصائية. والنتيجة من هذا البحث هي وجد الباحث تأثير باستخدام البطاقة الومضية بالحروف الهجائية في استيعاب المفردات، ومن النتيجة بعد أن قام بالاختبار البعدي بين فصلين: في الفصل التجريبي بالمعدل (77,5) والفصل الضابطي بالمعدل (65,90). فوجد الباحث نتيجة باختبار-ت (To) = 2,36 أكبر من النتيجة الجدول (Tt) في الدرجة 5%= 1,99. والخلاصة، استخدام البطاقة الومضية بالحروف الهجائية لها آثار في استيعاب المفردات لدى الطلاب في الفصل الثاني بمدرسة المتوسطة محمدية لانجسا.